Description of the adult and larva of Clunio balticus Heimbach, 1978 (Diptera, Chironomidae) from the seashore of Bergen (Norway) - Moubayed-Breil, Joel; Michailova, P. (Zootaxa, 2020)
The male and female adult and larva of Clunio balticus Heimbach, 1978 are diagnosed and described based on reared material, which was collected in the marine littoral zone along the coast of Bergen (Norway). Male and female adults and larvae of C. balticus can be easily distinguished from other known European Clunio species on the basis of some atypical features found in the male and female adults and fourth instar larvae. The biological cycle (reproduction and emergence) of C. balticus is a slight semilunar-periodic synchronization on days near the high tides. C. balticus is a local biogeographic representative of the northern Atlantic coast, which includes the eastern and western seashores. Remarks on related known Clunio species from Europe with comments on the ecology and geographical distribution of C. balticus are given.